ВІТРОЕНЕРГЕТИКА В ПОЛЬЩІ - Долera, В. (Інститут електродинаміки НАН України, Київ, 2012)
The process of current and future wind power development in Poland is analysed. Analysis and assessment of wind power market in Poland in technical, economical and environmental aspects is made. Perspectives of wind power development up to 2020 in context of the implementation of the EU's "3 x 20%" climate package by Poland and national quantitative target for RES development by year 2020 are described. References 6, tables 2.